KAJIAN POROSITAS TANAH PADA PEMBERIAN BEBERAPA JENIS BAHAN ORGANIK DI PERKEBUNAN KOPI ROBUSTA - Johandre Arpindra Surya; Yulia Nuraini; W Widianto (Jurnal Tanah dan Sumberdaya Lahan, 2017)
Organic matter application can improve to soil structure. The purpose of this study was to explore Â the effects of application of various organic matters (cow manure, vermicompost and coffee fruit skin) to soil total porosity in plantation-based robusta coffee (PTPN XII) Bangelan , Wonosari, Malang. The study was conducted using a factorial randomized block design and nested design pattern with the first factor was the type of fertilizer treatment (type of organic matterr), i.e. P1 (plot applied with vermicompost), P2 (plot applied with rind coffee), P3 (plot applied with cow manure), and P4 (plot applied with NPK / control). The second factor was the depth of soil, i.e. K1 (0-10 cm depth), K2 (10-20 cm depth), and K3 (20-30 cm depth). Parameters observed were soil texture, soil bulk density, soil bulk density, soil porosity, soil organic C, and soil pH. The results showed that application of organic materialss (cow manure and vermicompost) was able to improve total porosity of the soil. C-organic content of the soil was Â highest at the plot applied with vermicompost.